Pengembangan Sistem Informasi Manajemen Terintegrasi Berbasis Web untuk Optimalisasi Operasional dan Pengambilan Keputusan Strategis pada UMKM - Nurhidayati; Suhartini; Almi Yulistia Alwanda (Infotek: Jurnal Informatika dan Teknologi, 2026)
In the digital era, the utilization of information technology—including Management Information Systems (MIS)—is crucial for operational efficiency, data management, and strategic decision-making, particularly for MSMEs. Pesona Cafe Lenek, an MSME in East Lombok, continuously strives to enhance its customer service; however, its reliance on manual transaction processes has proven to be neither effective nor efficient. This study aims to develop a web-based management information system to improve the cafe's operational management and serve as a basis for strategic decisions regarding sales and employee payroll. The system also incorporates features for employee attendance tracking and accounting functions, specifically the general ledger and profit/loss statements. Implementing this information system is expected to streamline transactions, simplify the process of summarizing sales data, and enable faster access to financial and purchasing reports—whether on a monthly or on-demand basis. The results demonstrate that the platform enhances efficiency in promotions and ordering while strengthening the MSME's image through a user-friendly, informative interface. Furthermore, it provides an interactive user experience, expands market reach, and facilitates the sustainable management of sales data and digital marketing strategies. Ultimately, this boosts business competitiveness, fosters customer loyalty, and opens up new collaboration opportunities in the era of digital transformation.